Patient Satisfaction and Intention To Revisit Outpatient Specialist Clinic at XYZ Hospital, Bekasi City - Rifa, Alissa; Bernarto, Innocentius (School of Business, Bogor Agricultural University (SB-IPB), 2023)
This research was done as a response to the discrepancy between the target and the actual revisitations to the specialized outpatient clinic at XYZ Hospital in Bekasi City, then hoping to improve revisit intention at XYZ Hospital in Bekasi City. Several theories suggest that an increase in patient satisfaction leads to an increase in revisit intention. Patient satisfaction itself is related to hospital's physical environment, registration service, waiting time, doctor service, and nurse service. The aim of this study is to find out the positive impact of those variable towards patient satisfaction and then revisit intention. The model used in this study was adapted from previous research that was empirically tested on the population of patients at the specialized outpatient clinic at XYZ Hospital in Bekasi City. This study is a quantitative cross-sectional study. A questionnaire, made from prior interviews, was used to gauge hospital's physical environment, registration service, waiting time, doctor service, and nurse service. Respondent data were collected using purposive sampling with a total of 400 respondents. The data were analyzed using the PLS-SEM method. The results of the study showed that the hospital's physical environment, registration service, waiting time, doctor service, and nurse service have a positive influence on patient satisfaction. In addition, patient satisfaction also has a positive influence on revisit intention. In conclusion, this study proved that hospital’s physical environment, registration service, waiting time, doctor service, and nurse service have a positive impact on patient satisfaction which in turn had a positive impact on patient’s revisit intention. Keywords: doctor service, nurse service, outpatient specialist, patient satisfaction, revisit intention